STOCK ASSESSMENT OF SOLDIER CATFISH OSTEOGENEIOSUS MILITARIS ALONG THE NORTHWEST COAST OF INDIA - GULATI, DEEPAK; DEVARAJ, M.; PALANISWAMY, R. (Journal of Indian Fisheries Association, 2015)
Value of length growth parameters Loo, K and t 0 from age-length relation obtained from length-frequency analysis for the soldier catfish stock were estimated to be 47.6 em, 0.51 per year and 0.03 year respectively. The age at recruitment (tr) ws 0.58 year and the age at first capture (tc) 0.83 year. The total mortality (Z) was 0.88 including the present natuiÂ·al mortality (M) of 0.84 and fishing mortality (F) of 0.04. The total stock of this fish along the Northwest coast of India was assessed to be 32,413 tons and the MSY 5,426 tons which is much higher than the current catch of 863.8 tons. The potential yield (P Y) of 38.7 g per recruit could be obtained at the optimum of exploitation (ty) of 2.84 years.